Diretrizes para o design de soluções computacionais cientes da sustentabilidade - Oliveira, Renata Rodrigues de (2018)
Sustainability is a subject that has gained visibility through international discussions and concern for the future. When talking about sustainability, it must be understood in terms of both environmental and social and economic aspects, emphasizing its scope. Computational solutions are consumer goods and herefore it is the responsibility of the software and hardware industry, as well as its designers and developers, to reflect and act so that computer solutions are aware of sustainability issues. The literature exposes everal works in the line of sustainable design, authors such as Blevis, Baranauskas and Fallman discuss the theme, however few are dealing with sustainability in design, and in particular computing is still in the first steps. Therefore, a set of recommendations was formalized to guide the designers of computational solutions in the creation of these solutions, so that the aspects of sustainability in design are already considered. The methodology adopted includes bibliographical studies, a questionnaire on the subject applied to the computer community, a diagram of affinities and a look at other areas of knowledge that already have consolidated methods on sustainability; such as ISO standards; for the construction of the guidelines. After creation, the guidelines were applied to the academic and business scenario. The evaluation of the resulting solutions occurred by one method; the product of a master’s degree dissertation in the same area of study, and the evaluation of three experts by the guidelines applied, which was satisfactory and generally changed the opinion of the people who participated in the study. With the help of guidelines, it is possible to think about how to design sustainable solutions that respect the continuity of life.